Entrepreneurial awareness, entrepreneurial self-efficacy, viable business plan and SMEs’ performance in north-western Nigeria: the moderating role of access to finance - Shamsudeen, Kabir (2017)
SMEs are essential to economic growth in Nigeria and are assumed to be a major source of employment, contributing significantly to the country‘s gross domestic product. The purpose of this study is to examine the moderating role of access to finance (AF) on the relationship between entrepreneurial awareness (EAW), entrepreneurial self-efficacy (ESE), viable business plan (VBP), and performance of small and medium enterprises (SMEs) in north-western Nigeria. Even though the relationships have generated significant scholarly interest, few studies have been conducted among the SMEs in Nigeria. The unit of analysis in this study was the organisation, which was the SMEs in Nigeria and the owners/managers of the SMEs were the participants. The study employed the cluster sampling technique and data were collected randomly using the drop-off and collect method. 559 questionnaires were distributed using the cross-sectional research design. After the screening, a total of 354 questionnaires were deemed completed and usable. SmartPLS 2.0 was employed to analyse the data. The findings of this study revealed that EAW and VBP had direct significant relationships with SMEs‘ performance in Nigeria while ESE was found not to be a predictor of performance. Of the moderating relationships, AF was found to moderate those between VBP and SME‘s performance but exerted no moderating effect on the relationships between EAW, ESE, and SMEs‘ performance. This study contributes to the extant literature on how AF moderates such strategic resources and SMEs‘ performance relationships. Finally, the study‘s implications for theory and practice, limitations, conclusions as well as the direction for future research are provided and discussed.